2015
DOI: 10.1890/14-1943.1
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity effects and rates of spread of nonnative eucalypt woodlands in central California

Abstract: Woodlands comprised of planted, nonnative trees are increasing in extent globally, while native woodlands continue to decline due to human activities. The ecological impacts of planted woodlands may include changes to the communities of understory plants and animals found among these nonnative trees relative to native woodlands, as well as invasion of adjacent habitat areas through spread beyond the originally planted areas. Eucalypts (Eucalyptus spp.) are among the most widely planted trees worldwide, and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…We found that the body condition index of salamanders in Eucalyptus forest was significantly lower than those found in Quercus woodlands. The effect on body condition is consistent with prior work demonstrating a negative effect of introduced Eucalyptus on amphibian diversity (Fork et al, 2015;Russell & Downs, 2012). Importantly, our results also suggest that although Eucalyptus may not always decrease amphibian abundance or diversity (Keane & Morrison, 1990;Sax, 2002), it can have more cryptic negative effects.…”
Section: Potential Effects Of Eucalyptus Invasion On Batrachoseps Attsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the body condition index of salamanders in Eucalyptus forest was significantly lower than those found in Quercus woodlands. The effect on body condition is consistent with prior work demonstrating a negative effect of introduced Eucalyptus on amphibian diversity (Fork et al, 2015;Russell & Downs, 2012). Importantly, our results also suggest that although Eucalyptus may not always decrease amphibian abundance or diversity (Keane & Morrison, 1990;Sax, 2002), it can have more cryptic negative effects.…”
Section: Potential Effects Of Eucalyptus Invasion On Batrachoseps Attsupporting
confidence: 91%
“…Although we cannot determine what proximate factor is driving body condition decline in Eucalyptus habitat, there are multiple possible explanations including decreased prey availability. For example, Fork et al (2015) found lower arthropod richness and lower abundance of some arthropod classes in Eucalyptus relative to oak woodland habitat-although an earlier study did not find differences in leaf litter arthropod richness in Eucalyptus vs. Quercus woodlands; Sax, 2002. In addition, Eucalyptus leaf extract has been found to compromise chemical communication in salamanders, and this could contribute to stress in Batrachoseps residing in invasive vegetation dominated habitat (Iglesias-Carrasco et al, 2017).…”
Section: Potential Effects Of Eucalyptus Invasion On Batrachoseps Attmentioning
confidence: 92%
See 1 more Smart Citation
“…Greatest dispersal distances for individual stands, estimated from the report's maps for this review, ranged from zero for roadside plantings (Site 14) to 133 m (Site 9). Similarly, Fork et al (2015) analysed the spread of six eucalypt stands in the Elkholm Slough watershed (California). They found an average increase of 271% over 70 years , which was almost identical to that reported for the stands at Angel Island (i.e.…”
Section: Evidence Of Seed Dispersal From Eucalypt Stands Outside Austmentioning
confidence: 99%
“…At the turn of the 19 th century, E. globulus was introduced to California to provide a new supply of timber (Santos, 1997; Farmer, 2013), and, despite its limited viability as a timber species, continues to occupy ~16,000 hectares of the state (Ritter and Yost, 2009). In these plantations, plant understory diversity is low (Westman, 1990; Fork et al, 2015), and allelopathy is credited, both anecdotally (DiTomaso et al, 2013; Nash, 2013; McBride, 2014; Nance, 2014) and in the literature (Baker, 1966; del Moral and Muller, 1969; May and Ash, 1990; Becerra et al, 2018), as the mechanism by which native understory vegetation is inhibited.…”
mentioning
confidence: 99%